(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The rapid development of financial markets caused the growth of an interest in alternative investments into raw materials, in particular of agricultural origin. Especially agricultural derivatives, on account of their securities of future financial benefits on the real market, constituted the effective tool in the diversified investment portfolio. Investment funds started to enable the access to markets of raw materials for individual investors with index funds in search for above average returns on investment. A destabilization of international commodity markets is an effect of this action through the limitation of the prediction of prices. This research is on an increase of the market risk, measured with the changeability of prices on the market of cereal crops.